Comprehensive Treatment of Functional Dyspepsia Using Traditional Chinese Medicine: A Review Based on Pathophysiological Perspectives - Fan M; Pan X; Liu Y (Drug Design, Development and Therapy)
Mingming Fan,1 Xiangbin Pan,2 Yingzhe Liu3 1Department of Geriatric, Heilongjiang Academy of Traditional Chinese Medicine, Harbin, Heilongjiang, People’s Republic of China; 2Department of Spleen, Stomach and Hepatobiliary, Second Affiliated Hospital of Heilongjiang University of Chinese Medicine, Harbin, Heilongjiang, People’s Republic of China; 3First Department of Endocrinology, First Affiliated Hospital of Heilongjiang University of Chinese Medicine, Harbin, Heilongjiang, People’s Republic of ChinaCorrespondence: Yingzhe Liu, First Department of Endocrinology, First Affiliated Hospital of Heilongjiang University of Chinese Medicine, 26 heping Road, Harbin, Heilongjiang, People’s Republic of China, Email lyzkyyxscience@163.comAbstract: Functional dyspepsia (FD) is a common functional gastrointestinal disorder characterized by epigastric pain and symptoms related to meal consumption. According to recent diagnostic criteria, FD can be classified as epigastric pain syndrome (EPS) or postprandial discomfort syndrome (PDS), based on the predominant symptoms. The pathophysiology of FD can be influenced by various factors, including microinflammation, gastrointestinal infections, abnormal gastroduodenal motility, visceral hypersensitivity, disturbances in the brain-gut axis, and psychological factors. As a result, its management requires a comprehensive approach that includes both pharmacological and non-pharmacological interventions such as psychological therapies and adjunctive treatments. However, despite the availability of various treatment options, no contemporary pharmacological agents have been approved specifically for FD. In this context, Traditional Chinese Medicine (TCM) has emerged as a promising alternative that offers notable efficacy and safety in managing FD. Various TCM modalities, including herbal prescriptions, acupuncture, moxibustion, and music therapy have demonstrated therapeutic potential. In this article, we discuss the pathophysiology of FD from a modern medical perspective and describe integrative treatment strategies based on TCM, highlighting the potential benefits of combining the traditional and contemporary approaches.Keywords: FD, EPS, PDS, duodenum, TCM